PENGARUH MEDIA INTERAKTIF ANIMASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V SDN GONDRONG 2 - Krisdayanti; Ino Budiatman; Nurul Muttaqien (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine whether or not there is an influence of interactive animated media on student learning outcomes in science subjects. The method used in this study is Quasi Experimental and Conventional. The hypothesis put forward in this study is: "There is an influence on the learning outcomes of science students who are taught using interactive animated media." This research was conducted at SDN Gondrong 2 Tangerang class V in the odd semester of the 2022-2023 academic year. The sample studied was 64 students consisting of 32 students in the experimental class and 32 students in the control class. The independent variable in this study is the animated interactive media and the dependent variable is student learning outcomes. Previously, this research instrument was given to the object of research. The instrument was tested first, namely the validity and reliability trials were proven to be valid & reliable. The study showed that the results of the final test of the experimental class and the control class with the Paired Sample Test T-test obtained a (2-tailed) value of 0.000 and sig. 0.05 the results of this study concluded that there was an influence on student learning outcomes by using interactive animated media with students who were taught by conventional models.